In-situ TEM investigation of defect evolution in FeCrAl during post-irradiation annealing - Yuntai Luo; Changyong Zhan; Yuxin Zhong; Yu Zou; Ruiqian Zhang; Jijun Yang (Journal of Materials Research and Technology, 2023)
Aiming to newly-developed FeCrAl alloys for accident-tolerant fuels (ATF) in light water reactors (LWR), an in-situ investigation of scan transmission electron microscopy (STEM) observation and annealing was performed in order to understand the evolution of radiation-induced defects (RID) and the Cr segregation during elevating the temperature. In this study, the FeCrAl alloys were irradiated with 6Mev Au+ ions up to a dose of 10 dpa at 400 °C, and the RID in depth of 1 μm were assess by in-situ TEM during annealing. A Cr layer, the dislocation loop raft and Cr-decorated dislocation loops were formed in the near-surface region I. Cavities, Cr-rich precipitates were formed in the interior region II. By calculating thermal equilibrium vacancies theoretically, the cavity formation is ascribed to the surface effect of the foil and the damage of TEM electrons. Shrinkage of some loops could be ascribed to produced vacancies. Formations of the raft and Cr-decorated loops are due to the strain or stress constructed by the surface C species or damages when annealing below 500 °C. The pronounced Cr-rich precipitates during 550–600 °C are due to the Cr atomic segregation initiated by vacancies via a long-time recovery towards low-energy sites. This work indicates the defect-caused stress profile is important for the Cr segregation.